Trends in sensing of creatinine by electrochemical and optical biosensors - Radhika Babasaheb Jadhav; Tejaswini Patil; Arpita Pandey Tiwari (Applied Surface Science Advances, 2024)
Creatinine is the by-product of creatine phosphate within the muscle, supplying energy to the muscle tissues. It is imperative to clinically assess creatinine levels in both urine and blood as it serves as an indicator of renal, muscle, and thyroid functionality. The point-of-care medical diagnostic research and development is the most innovative form of exploratory research. The determination of creatinine can be achieved through several traditional methods such as colorimetric, spectrophotometric and chromatographic techniques. Although these method offers high sensitivity and selectivity, they are accompanied by drawback such as long analysis time, the need for sample pre-treatment, expensive instruments and skilled personnel. In contrast, sensors and biosensors present a favourable solution to these limitations as they offer rapid, user-friendly, cost effective and highly sensitive alternatives. This review article describe recent trends in creatinine detection by using electrochemical and optical biosensors, advantages and disadvantages of biosensors. This review highlights the wide detection range of creatinine and explore the commercialization aspects of biosensors with in home monitoring system.